Translation and validation of Bahasa Malaysia version of Urogenital Distress Inventory (UDI-6) and Incontinence Impact Quality of Life Questionnaires (IIQ-7), a cross sectional study - Nusee, Zalina; Ab Rahman, Jamalludin; Abdulwahab, Dalia F; Ismail, Rozihan (Universiti Sains Malaysia, 2016)
Background: Urinary incontinence (UI) demonstrates major prevalence in women of different population groups. Reduced quality of life (QOL) is observed due to incontinence problems. Urogenital Distress Inventory (UDI-6) and Incontinence Impact Quality of Life (IIQ-7) are useful disease-specific questionnaires evaluating the impact of urinary incontinence on the QOL of women which is accepted internationally. Objective: This study aims to translate and validate UDI-6 and IIQ-7 in Malay language. Methods: A cross sectional study, which recruited 100 participants from two urogynecology clinics. Both questionnaires were initially translated from English to Bahasa Malaysia followed by back translation and final correction done by the professional translators. The participants were requested to maintain a urinary record of the upcoming week for three days that assisted in quantifying the severity of symptoms. None of the subjects were assigned any treatment during the study period. Validity and reliability of the translated questionnaires were determined by checking the internal consistency and also by doing test-retest. Results: The internal consistency levels of the UDI-6 and IIQ-7 Bahasa Malaysia questionnaires were 0.73 and 0.90 respectively with good test-retest (0.86 and 0.95). Incontinence episodes were strongly associated with obstructive, irritative, and stress symptoms. The factor of day time voiding had strong correlation with obstructive and irritative symptoms. Conclusion: UDI-6 and IIQ-7 did not measure similar outcomes; however, both questionnaires have their strengths in clinical settings. Analysis has also revealed that the Malaysian versions of both questionnaires had appropriate test-retest validity and reliability. Thus, it can be said that both of the questionnaires had great importance for screening patients with urinary incontinence in Malaysia.